2011
DOI: 10.1371/journal.pone.0021032
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Algicidal Bacterium Kordia algicida with Diatoms: Regulated Protease Excretion for Specific Algal Lysis

Abstract: Interactions of planktonic bacteria with primary producers such as diatoms have great impact on plankton population dynamics. Several studies described the detrimental effect of certain bacteria on diatoms but the biochemical nature and the regulation mechanism involved in the production of the active compounds remained often elusive. Here, we investigated the interactions of the algicidal bacterium Kordia algicida with the marine diatoms Skeletonema costatum, Thalassiosira weissflogii, Phaeodactylum tricornut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(155 citation statements)
references
References 44 publications
8
147
0
Order By: Relevance
“…These results suggest that C. atlanticus does not constitutively release a growth inhibitor into MB under these conditions, at least at an effective concentration. By contrast, another study showed that the flavobacterium Kordia algicida constitutively secretes a protease that negatively impacts several diatoms (Paul and Pohnert, 2011). One diatom, Chaetoceros didymus, appears to deactivate the algicidal activity of K. algicida through production of its own counter-acting protease-degrading enzymes (Paul and Pohnert, 2013).…”
Section: Effect Of Croceibacter Atlanticus On Diatoms Hm Van Tol Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…These results suggest that C. atlanticus does not constitutively release a growth inhibitor into MB under these conditions, at least at an effective concentration. By contrast, another study showed that the flavobacterium Kordia algicida constitutively secretes a protease that negatively impacts several diatoms (Paul and Pohnert, 2011). One diatom, Chaetoceros didymus, appears to deactivate the algicidal activity of K. algicida through production of its own counter-acting protease-degrading enzymes (Paul and Pohnert, 2013).…”
Section: Effect Of Croceibacter Atlanticus On Diatoms Hm Van Tol Et Almentioning
confidence: 98%
“…Beneficial bacteria typically provide a useful service to the diatom in exchange for organic nutrients; for example, Ruegeria pomeroyi provides vitamin B 12 to Thalassiosira pseudonana in exchange for the organic sulfur compound 2,3-dihydroxypropane-1-sulfonate . Many detrimental bacteria are from the phylum Bacteroidetes or the class Gammaproteobacteria (Mayali and Azam, 2004) and are thought to harm phytoplankton by secreting proteases or other algaecides (Lee et al, 2000;Paul and Pohnert, 2011;Seyedsayamdost et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…or Pseudomonas veronii, present in H2 and CC7, respectively. Kordia is an algicidal bacterium (Sohn et al, 2004) capable of inhibiting the growth of diatoms, and even killing them by active lysis (Paul and Pohnert, 2011). Its ubiquity and high abundance (37%) in the H2 core microbiome indicates that these bacteria might be important for the host; however, this has to be studied in more depth.…”
Section: Exaiptasia H2 and Cc7 Strains Only Share A Small Common Micrmentioning
confidence: 99%
“…AHLs have also been identified in marine surface-associated microbial communities (Decho et al, 2009;Huang et al, 2009). The bacterium Kordia algicida relies on QS-dependent excretion of an algicidal protein to suppress activity of marine diatoms such as Skeletonema costatum, Thalassiosira weissflogii and Phaeodactylum tricornutum (Paul and Pohnert, 2011). Algicidal bacteria, such as K. algicida, may contribute not only to the termination of algal blooms, but also to the release of algal particulate organic carbon (POC) and DOC, thus influencing the MCP process.…”
Section: Quorum Sensingmentioning
confidence: 99%